2016
DOI: 10.29063/ajrh2016/v20i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Teen Pregnancy in sub-Saharan Africa: A Multi-Country Cross-Sectional Study

Abstract: This study aimed to assess the contextual factors associated with teenage pregnancy in sub-Saharan Africa. Using DHS data we modelled females aged 15-19 with multilevel logistic regression to establish the independent influence of social disadvantage on teenage pregnancy in West, East and Southern Africa with aid of the MLwiN programme. Results showed teenage pregnancy decreased in East Africa, plateaued in West Africa and increased slightly in Southern Africa between 1992 and 2011. Multilevel multivariate reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 36 publications
(40 reference statements)
11
67
2
Order By: Relevance
“…This analysis found that teenage women with secondary education were less likely to have pregnancy. This result is similar to other studies in some other African countries (Ayele, 2013;Odimegwu & Mkwananzi, 2016;Rosenberg et al, 2015). Although many studies have found such an association, a causal relationship cannot be definitively established.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This analysis found that teenage women with secondary education were less likely to have pregnancy. This result is similar to other studies in some other African countries (Ayele, 2013;Odimegwu & Mkwananzi, 2016;Rosenberg et al, 2015). Although many studies have found such an association, a causal relationship cannot be definitively established.…”
Section: Discussionsupporting
confidence: 91%
“…Existing evidence suggests a long list of possible risk factors contributing to teenage pregnancies, including low education level, lack of negotiation skills, insufficient parental supervision, not using contraceptive methods, age at marriage, religion, residing in rural versus urban areas, peer pressure, and lower economic status (Ajala, 2014;Christofides et al, 2014;Kanku & Marsh, 2014;Moni, Nair, & Devi, 2013;Neal, Chandra-Mouli, & Chou, 2015;Okigbo & Speizer, 2015;Rutaremwa, 2013). In addition, teenagers living in households headed by single females or in families with poor family relationships are at higher risk of getting pregnant (Odimegwu & Mkwananzi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides economic factors (directly) leading to child marriage, we found that economic hardship had an effect on young people’s sexual behaviour, leading to teenage pregnancy and later on, marriage. A study using Demographic and Health Survey data in sub-Saharan Africa confirms that community poverty is associated with teenage pregnancy [ 24 ]. Transactional sex was found to take place frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood mortality reflects Social Economic Status (SES) and Quality of Life (QoL). In developing countries, mortality rates are not only affected by social, economic, demographic, and health variables, but also vary across regions and districts (Odimegwu & Mkwananzi, 2016). Globally, nearly 7 million children die each year before they reach their fifth birthday.…”
Section: Introductionmentioning
confidence: 99%